Prescribed opioid use is associated with adverse cardiovascular outcomes in community-dwelling older persons - Liew, S.M.; Chowdhury, Enayet; Ernst, M.E.; Gilmartin-Thomas, J.; Reid, Christopher; Tonkin, A.; Neumann, J.; McNeil, J.J.; Kaye, D.M. (WILEY PERIODICALS, INC, 2022)
Aims: Prescribed opioids are commonly used in the older community-dwelling population for the treatment of chronic pain. Although the harmful effects of opioid abuse and overdose are well understood, little is known about the long-term cardiovascular (CV) effects of prescribed opioids. The aim of this study was to investigate the CV effects associated with prescribed opioid use. Methods and results: A post hoc analysis of participants in the Aspirin in Reducing Events in the Elderly (ASPREE) trial was conducted. Participants in the ASPREE trial included community-dwelling older adults without a prior history of CV disease (CVD). Prescribed opioid use was defined as opioid use at baseline and/or at the first annual visit (AV1). Cox proportional hazards regression was used to calculate hazard ratios and 95% confidence intervals (95% CI) for associations between opioid use and CVD events following AV1. Of the 17 701 participants included (mean age 75.2 years, 58.2% female), 813 took opioids either at baseline or at AV1. Over a median follow-up period of 3.58 years (IQR 2.50–4.62), CVD events, most notably heart failure hospitalization, occurred in 7% (n = 57) amongst opioid users and 4% (n = 680) amongst non-opioid users. After adjustment for multiple covariates, opiate use was associated with a 1.67-fold (CI 1.26–2.23, P < 0.001) increase in the hazard ratio for CVD events. Conclusions: These findings identify opioid use as a non-traditional risk factor for CVD events in community-dwelling older adults.